Processos de voçorocamento na Bacia Hidrográfica do Ribeirão Vai Vem (Ipameri-GO) - Rocha, Erica Aparecida Vaz (2012)
The main objective of this study was to generate a model of susceptibility to the occurrence of gullies using parameters of the permanent physical environment. For the generation of this model, relevant parameters were chosen, which believe explain the occurrence of gullies, which were assigned values according to their influence on the erosion process. The following parameters were analyzed: slope, forms the slopes, soil and land use, which are represented by means of thematic maps were combined resulting in the final product which is the susceptibility map of the occurrence of gullies in Vai Vem River Basin (Ipameri / GO). These parameters were determined based on relevant literature and field work. The proposed methodology for the generation of this model of susceptibility to the occurrence of gullies was based on the use of ArcGIS 9.2, which allowed the creation of a database where the stored maps, images, statistical data, allowing the structure and its subsequent analysis. Once formed the basis for spatial data, we proceeded to a weighted correlation with other selected factors, with the ultimate goal, to carrying out a rigorous mapping of susceptibility against the appearance of gullies. For the physical characterization of the Vai Vem River Basin (Ipameri / GO) were used the morphometric analysis that began by ordering the fluvial channels and then the analysis of the geometrical characteristics of the drainage network and hypsometric analysis. It was made a sectorization of the basin using the criteria hydrographic, hypsometric and slope, to identify the differences in the asymmetry in the spatial arrangement of the drainage network. By analyzing the model and its validation in the field allowed to make some observations about the association of local characteristics and the occurrence of gullies.